Kilka uwag o wartościowaniu w komentarzach internetowych - Laskowska, Elżbieta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Based on a sample of comments gleaned from the Onet.pl portal, the author discusses positive and negative evaluations (axiological charge) found in internet language, and she examines some of the language devices used in such evaluations. In internet comments, it is definitely negative evaluation that prevails, and the positive evaluation of a single object creates only a background for a negative object. Samples which encode aggression and insults can also be found in the data. In the material under inspection, Internet users mploy all sorts of language devices used in an evaluative function; most of them are illustrative of economic, social and ethical values. Along with these values, emotions are also frequently expressed. Internet users resort to all sorts of language devices to signal evaluative functions, a number of them are marked and illustrate a colloquial style.